The Economic Effects of NASDAQ: Some Preliminary Results - Santomero, Anthony M. (Journal of Financial and Quantitative Analysis, 1974)
On February 1, 1971, the National Association of Security Dealers instituted an automatic quoting system for over-the-counter stocks. Heralded as a major advance in the elimination of market imperfections, the National Association of Security Dealers Automatic Quote System (NASDAQ) allowed bidand- ask prices of different firms in this geographically dispersed market to be centralized. Essentially its operation allowed individual “houses” to obtain the various bid-and-ask prices of market makers for a given unlisted security.